2019
DOI: 10.1111/iwj.13220
|View full text |Cite
|
Sign up to set email alerts
|

Aged garlic extract preserves cutaneous microcirculation in patients with increased risk for cardiovascular diseases: A double‐blinded placebo‐controlled study

Abstract: Laser Doppler velocimetry estimates tissue perfusion providing a record of microvascular blood flow. Patients with heart disease or diabetes mellitus have impaired microvascular perfusion leading to impaired wound healing. Aged garlic extract (AGE) has a positive effect on vascular elasticity. This study aimed to assess the effect of long‐term treatment with AGE on cutaneous tissue perfusion. A total of 122 patients with Framingham Risk Score ≥ 10 were randomised in a double‐blinded manner to placebo or 2400 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
5
27
0
3
Order By: Relevance
“…Our study showed that S1PC decreased the phosphorylation level of GEF-H1 and suppressed the interaction of GEF-H1 with RhoA and Rac (Figure 2). Taken together, these results showed that S1PC protected the barrier dysfunction elicited by TNF-α through inhibiting the phosphorylation and activation of GEF-H1 ( Figure 5), and suggested that this effect of S1PC is associated with the bene cial effect of AGE on atherosclerotic patients observed in the clinical studies [22][23][24].…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Our study showed that S1PC decreased the phosphorylation level of GEF-H1 and suppressed the interaction of GEF-H1 with RhoA and Rac (Figure 2). Taken together, these results showed that S1PC protected the barrier dysfunction elicited by TNF-α through inhibiting the phosphorylation and activation of GEF-H1 ( Figure 5), and suggested that this effect of S1PC is associated with the bene cial effect of AGE on atherosclerotic patients observed in the clinical studies [22][23][24].…”
Section: Discussionsupporting
confidence: 53%
“…Accordingly, the proper maintenance of barrier function may help protect the blood vessels from risk factors of vascular diseases. In addition, the protective effect of S1PC on vascular cells may explain in part the bene cial effect of AGE on the atherosclerotic patients in the clinical studies [22][23][24]. Effects of S1PC on cell permeability, junctional/cytoskeletal proteins, and MLC2 phosphorylation in TNFα-stimulated HUVECs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations